(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
An innovative teaching method, Game-Based Learning (GBL), has been shown to be effective in supporting teachers, particularly in Natural Science (IPA) subjects. This study examines how GBL is applied and its effects on science education in schools. To achieve this, a Systematic Literature Review (SLR) was conducted, analyzing scientific articles published from 2023 to 2025. The findings reveal that the GBL approach can significantly boost student motivation and active engagement, while also simplifying their grasp of complex and abstract science concepts. The success of GBL is highly dependent on selecting diverse and relevant learning media. Therefore, integrating GBL with suitable media presents a promising strategy for enhancing the quality of science education. Based on these implications, the study suggests that educators and educational media developers should continue to innovate by creating engaging, interactive media that aligns with science content to make the teaching and learning process more effective. It is hoped that these findings will guide teachers in choosing the right approach and help students understand science concepts in a more enjoyable manner.